THE ROLE OF INTERACTIVE METHODS IMPORTANCE OF ENGLISH COMMUNICATION FOR ENGINEERING STUDENTS - Pulatova Odina Khamidovna (Journals Park Publishing, 2022)
The importance of teaching English communication for engineering students discussed in the article. The world is developing in field of science and technology. Scientific inventions in Germany, France, and Russia cannot reach India through any language other than English. Therefore, a scientific invention in Germany or Russia will have become outdated and old by the time it reaches to Indian scientists through translation.The world is developing in field of science and technology. Scientific inventions in Germany, France, and Russia cannot reach India through any language other than English. Therefore, a scientific invention in Germany or Russia will have become outdated and old by the time it reaches to Indian scientists through translation.
Keywords: communication; brainstorming; conflict of ideas